Creative accounting, aggressive accounting and accounting fraud – auditors’ perception - Dobroszek, Justyna; Wnuk, Adrianna (Rachunkowość kreatwna i rachunkowość agresywna a fałszerstwo księgowe – percepcja biegłego rewidenta, 2022)
Creative accounting and aggressive accounting are perceived differently among researchers. On the one hand, they are treated as the same concepts, while on the other as independent, or are presented as similar points. In Polish publications, one can find an approach that aggressive accounting is convergent with accounting fraud, and is a negative part of creative accounting which also has a positive dimension. This paper aimed to reveal statutory auditors’ perceptions of creative accounting, in particular, as well as aggressive accounting and accounting fraud. A survey was conducted in November-December 2021 among 52 chartered accountants in Poland. The results indicate that the most recognised term among financial auditors is creative accounting, which they perceive mainly as manipulation, fraud or accounting falsification, and therefore negatively. In contrast, aggressive accounting is not known or identified by the respondents.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 2, s. 16-28
Keywords: creative accounting; aggressive accounting; accouting fraud; statutory auditor; perception; rachunkowość kreatywna; rachunkowość agresywna; fałszerstwo księgowe; biegły rewident; percepcja